Biomass gasification of hybrid seed Miscanthus in Glasgow's downdraft gasifier testbed system. (February 2019) - Kamble, Prashant; Khan, Zakir; Gillespie, Michael; Farooq, Mazin; McCalmont, Jon; Donnison, Iain; Watson, Ian
Abstract: Global energy problems, rise in CO2 emissions and their implications on climate change are well documented. Renewable energy provides a crucial role in reducing these emissions whilst providing sustainable energy; energy conversion of biomass forms a valuable part of a renewable energy portfolio, with capability for baseload provision, and gas and electricity production. Gasification is the thermochemical conversion of biomass (carbonaceous material) into producer gases. A small-scale throated downdraft gasifier was designed and manufactured at the University of Glasgow and built to easily assess the gasification performance under different conditions e.g. feedstock variety and with different instrumentation and control strategies. Various feedstock varieties of Miscanthus (OPM12, MxG, and OPM53) were gasified under the same equivalence ratio (ER 0.30). The elemental compositions of each Miscanthus varied with their genetic properties. A Gasifier Control Unit (G.C.U) was installed on the experimental gasifier to measure parameters: temperature, pressure, liquid flow and mass flow. The gasifier was operated in batch mode; to improve repeatability the throat, grate and assembly were cleaned after each experiment. The experimental work reported in this research is mainly focused on the comparative study and analysis of the producer gas compositions, carbon conversion efficiency, higher heating value (HHV), lower heating value (LHV), cold gas efficiency and gas yield with the different biomass feedstocks. The ultimate and proximate analysis was done for all Miscanthus varieties along with ash analysis. The major outcome of this research was to investigate the impact of feedstock variety on gasification performance and identify preferred Miscanthus varieties to grow at scale with optimised gasification.